The Effect of Bulb Extract from Dayak Onion (Eleutherine americana Merr) to the Cholesterol Level and the Trigliresida Level in Mice (Mus musculus) - Dina Karunia Binawati; Ngadiani (Future Science)
Bawang dayak or dayak onion (Eleutherine americana Merr) is an endemic plant from West Kalimantan. The bulb extract from dayak onion is known to be consumed as traditional medicine by dayak ethnic group. Dayak onion contained alkaloid, flavonoid, glycoside, saponin, and tannin that are very beneficial for health. This research aims to examine the effect of ethanol extract of dayak onion towards the cholesterol level and the triglyceride level in animal testing male mice (Mus musculus). This research uses completely randomized design with experimental laboratory methods by doing 5 treatments and 5 times replications. Mice are given mixed food consists of CP 511 concentrate and cow fat using 7:3 comparison for 10 days. Mice are also given treatment with the ethanol extract of dayak onion for 7 days with classifications of: negative control treatment, positive treatment, 50 mg/Kg BB, 100 mg/Kg BB, and 200 mg/Kg BB. The research result shows that the treatment of ethanol extract dayak onion has significant effect towards the decrease of triglyceride level in mice’s blood, but based on LSD test, the differentiation between each treatment is not significant. Based on the research result, ethanol extract of dayak onion according to the average result can indeed decrease the level of cholesterol, but the statistics test has not yet shown significant results